Temporal Relationship Between Pain and Mental Health Conditions Among Children and Young People—A Population-Based Register Study in Sweden - Bondesson, Elisabeth ; 0000-0003-0661-8242; Bolmsjö, Beata Borgström; Pardo, Fabian Larrosa; Jöud, Anna Saxne ; 0000-0001-7192-4911 (Journal of Pain, 2024)
Both pain and mental health conditions are common among young people. They often co-occur, but we wanted to investigate further whether it is pain (abdominal pain, headache, musculoskeletal pain, menstrual pain) that precedes mental health conditions (depression, anxiety, stress, phobia) or whether it is the other way around, mental health conditions that precede pain. Using electronic health records—the Skåne Healthcare Register—we identified and followed young people aged 7 to 18 over a 13-year period and tracked all their registered diagnoses. Using Poisson regression, we analyzed the incidence rate ratio (IRR) of being diagnosed with mental health conditions after an initial diagnosis of pain and vice versa the IRR of being diagnosed with pain after an initial diagnosis of a mental health condition. Among individuals with pain, 12,054 (23%) later received a diagnosis of a mental health condition. The IRR for a mental health condition after pain was 2.86 (95% (confidence interval) CI = 2.78–2.94) compared to not having pain, adjusted for age, sex, and prior health care consultations. Among individuals with mental health conditions, 3,688 (17%) later received a diagnosis of pain. The adjusted IRR was 1.57 (95% CI = 1.52–1.63). Compared to boys, girls had consistently higher estimates, and the same was found for the younger individuals compared to the older ones. Individuals with pain have a 3-fold increased risk of developing mental health conditions, while the risk of developing pain after mental health conditions was lower although still elevated compared to young people seeking care regardless of cause. Perspective: Young people with pain have a 3-fold increased risk of developing mental health conditions, while the reverse risk is lower but still elevated compared to young people without these conditions. Health care professionals must recognize the interplay between pain and mental health in young patients when diagnosing and planning treatment.
Keywords: Adolescents; children; electronic health record; mental health condition; pain